2020
DOI: 10.9734/ejmp/2020/v31i2030355
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Features, Mineral Contents, Anti-sickling, Antioxidant and Antibacterial Activities of Stem Bark of Harungana madagascariensis Lam. Ex Poiret (Hypericaceae)

Abstract: Aims: This study addressed the identification of bioactive compounds, the determination of mineral content and the evaluation of the antibacterial, antioxidant and anti-sickling activities of aqueous extract from stem bark of Harungana madagascariensis. Place and Duration of Study: Centre d’Etudes des Substances Naturelles d’Origine Végétale (CESNOV), Faculty of Pharmaceutical Sciences, University of Kinshasa and Faculty of Sciences, National Pedagogic University in DRC, between October 2018 and January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…In addition to these works, the results of investigations by (Fatokun et al, 2015; Mukeba et al, 2020) [30,31] on the antisickling activity of some Congolese and Nigerian medicinal plants respectively showed that aqueous and ethanolic extracts of H. madagascariensis inhibited HbS polymerization by 42% and reversed sickle cells by 52%. In addition, results from previous work (Tatiana et al, 2020) [32] showed that aqueous and ethanolic extracts of Z. leprieurii inhibited sickle cell formation by 89% and 81% respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to these works, the results of investigations by (Fatokun et al, 2015; Mukeba et al, 2020) [30,31] on the antisickling activity of some Congolese and Nigerian medicinal plants respectively showed that aqueous and ethanolic extracts of H. madagascariensis inhibited HbS polymerization by 42% and reversed sickle cells by 52%. In addition, results from previous work (Tatiana et al, 2020) [32] showed that aqueous and ethanolic extracts of Z. leprieurii inhibited sickle cell formation by 89% and 81% respectively.…”
Section: Discussionmentioning
confidence: 95%
“…These authors reported that the inhibition of falciformation generated by this extract was due to the presence of amino acids such as phenylalanine glutamic acid, arginine, Tyrosine and aspartic acid in varying concentrations. In addition, authors such as ( [28,29,30] claim that aromatic amino acids have antisickling activity. The presence of these amino acids in our plant extracts could participate in the fight against sickle cell disease by having a polymerization inhibition activity.…”
Section: Discussionmentioning
confidence: 99%
“…Vessels are involved in the transport system of the plant. Mukeba et al (2020) found similar calcium oxalate prisms in the stem bark powder of H. madagascariensis and stated that these are helpful in the detection of adulterants and in identification of herbal drugs. Parenchyma cells constitute the ground tissue, sclerenchyma cells give support to plant body and trichomes play a key role in sustaining water balance, reflect radiations, lower the plant temperature, and prevent water loss in the plants (Ishtiaq et al, 2018).…”
Section: Powder Drug Study Of D Mucronata and M Communis (Sem)mentioning
confidence: 98%
“…In developing countries where the population lives below $0.20/person/day [48,49]. The population practices self-medication by using certain non-steroidal anti-inflammatory eye drops in order to reduce or relieve pain).…”
Section: Symptomsmentioning
confidence: 99%